Mười năm phát triển lâm nghiệp Miền núi - Lung, Nguyen Ngoc (Nhà xuất bản nông nghiệp, 2016)
Forests provide a living environment, resources and employment, and any change to the area or quality of forests have direct impacts on the development of upland areas as well as of the whole country. In 1943, the forest area was 14,300 million hectare, covering 43% of the area of the territory. The corresponding figures in 1990 were only 9,175 million hectare and 27.8% coverage; and in the year 2000, 10,915 million hectare and 33.2% coverage. The average forest area per capita in 1943 was 0.70 hectare, and down to 0.14 hectare compared to the average of 0.42 hectare of ASEAN countries and 0.60 hectare of the world. In the last ten years, there has been an increase in the forest area, but the change has not been the same between different areas, and there has been a big decrease in Tay Nguyen and the eastern part of the South. Although the forest area in general has increased, the forest quality has continuously been degraded. Natural forests have become poorer and poorer with an 11% decrease in total reserve. Precious and hard wood species have been over exploited, birds and animals have been hunted to exhaustion, and many flora and fauna species are in the danger of becoming extinct as stated in the red books of Vietnam. It is assessed that only 2.4% of the remaining forests is rich forest, 15.1% is average forest, 46% poor forest and 36.5% young forests. Thus, poor forest and young forest account for over 80%. During the last ten years, implementing the policy of converting from highly State controlled forestry to a social forestry regime, the Government has allocated the right to use forest land with an increasing area to organisations and peasant households. Many forest farms and forest gardens have been formed and many peasant households have effectively used forest land in their business. The prospect of social forestry is thus can be expected to be promising. The paper includes statistics on forest areas in eight economic zones in the country which belong to various entities such as State owned forestry enterprises and companies, management boards of protective forests, management boards of speacialised forests, joint ventures, households, collectives, youth units, army units and so forth. State owned forestry enterprises and companies still use a very large area of forests (3,578 million of hectares). Together with households and collectives which use 2,006 million of hectares, these two types of entities use over 50% of the total forest area in the whole country. As of 1 January 2000, the most popular species in planted forests are Eucalyptus, Acacia, various types of pines and Melaleuca, accounting for 62% of the total 1,471 ha of planted forests. The 3 main functions of forests are environmental function, forestry product supply and social function. Regarding the environmental function, forests preserve biodiversity and different species of flora and fauna which live together with human beings. They serve as a long-term reserve for humans and thus have been the subject of an international convention on biodiversity (CBD). Vietnam is assessed as one of the countries rich in flora and fauna in the world due to its diversity in topography, climate and types of forests. Vietnam has established a system of specialised forests including 13 national parks, over 50 natural reserves and historical and 439 cultural forests. It is considered one of the countries which are poor but have implemented well the CBD,CITES and RAMSA international conventions. Forests themselves are a type of living environment, like land, water or air, but forests have the ability to govern and improve other environments which they have contact with, creating a sustainable environment for human life. The loss of forests has led to air temperature increase, a large amount of CO2, and very severe consequences in the form of storms, floods or droughts. The decrease in forest area and quality is thus a big danger which will lead to environment degradation. Therefore, the environmental function of forests must be considered the most important. The demand for forestry products and other raw materials has kept increasing in the development of the country. Such demand has reached up to tens of million of m3 of timber for furniture, for construction, for paper making, artificial timber, mine poles and so forth per year, and is estimated to be 13.5 million of m3 of timber in 2010. Our task is both to protect the existing forests and to develop new forests. Forests also contribute to the resolving of many other important social issues such as creating employment, improving the living standard of local inhabitants, creating a cultural environment with beautiful landscape. Especially, forests are the source of the spiritual and material life of ethnic minorities. Conclusion: Although the forest area and coverage in Vietnam in the year 2000 have been improved to a small extent compared to 5 or 10 years ago thanks to national and international efforts, we are still far from the target of 14.3 million hectares of forests (43% coverage) and quality forests in order to contribute to a development environment for Vietnam and the world. The immediate forestry strategy of Vietnam is to protect and develop forests in the social direction with human beings, especially upland and minority people, as its centre. This is a task of all citizens in every socio-economic sector. Two large, long term projects are the forest protection and restoration under the project for planting 5 million of hectares of forests (1998-2010) and sustainable management and certification of forests (1998-2010).